Characteristics of traumatic brain injury-related healthcare visits across social determinants of health: A population-based birth cohort study - Vincy Chan; Clarissa Serafine Wirianto; Robert Balogh; Juliet Haarbauer-Krupa; Michael David Escobar (PLoS ONE, 2025)
Background Traumatic brain injury is a major cause of death and disability worldwide, with almost half of new cases occurring in children, adolescents, and young adults. However, data on injury characteristics stratified by social determinants of health are scarce. This study explores severity, intent, and mechanism of traumatic brain injury sustained during childhood, adolescence, and young adulthood by social determinants of health. Methods This study utilizes a population-based birth cohort of births in publicly funded hospitals in Ontario, Canada, between April 1, 1992 and March 31, 2020 (n = 3,648,760). Individuals experiencing a traumatic brain injury requiring medical attention to the emergency department or acute care between April 1, 2002 and November 20, 2020 (n = 94,514) were identified using International Classification of Diseases Version 10 diagnosis codes. Social determinants of health variables included age, sex, rurality of residence, neighbourhood income quintile, and the following Ontario Marginalization Index variables: households and dwellings, material resources, and racialized and newcomer populations. The primary outcome was percentage of injuries falling under each mechanism, intent, and severity of injury category, stratified by social determinants of health variables. Results Approximately 50% of injuries were mild and 96.2% of injuries were unintentional. Injury severity and intent of injury significantly varied by social determinants of health; for example, the proportion of traumatic brain injury-related healthcare visits for moderate/severe and intentional injuries was highest in areas with the lowest income quintile (13.3% and 6.1%, respectively), lowest households and dwellings stability (12.2% and 5.7%, respectively), lowest material resources (12.8% and 6.0% respectively), and highest racialized and newcomer populations (13.5% and 4.5% respectively). The percentage of traumatic brain injury-related healthcare visits for a sports-related injury significantly varied by social determinants of health; for example, the proportion of traumatic brain injury-related healthcare visits for sports-related injuries was highest among males (45.5%), those living rural areas (44.0%), and those living in areas with the highest income (47.2%), highest households and dwellings stability (44.0%), highest material resources (45.8%), and lowest racialized and newcomer populations (43.4%). Conclusions Characteristics of traumatic brain injury-related healthcare visits vary based on social determinants of health. Targeted prevention of traumatic brain injury beyond the sports settings, including fall prevention among young children, are encouraged, and guidelines to identify and address traumatic brain injury outside of the sports setting must be developed to support early intervention of traumatic brain injury across social determinants of health.